Determinasi Faktor-Faktor Kesadaran Pengguna Mobile Banking terhadap Ancaman Keamanan Siber di Era Digital: Determining the Factors Influencing Mobile Banking Users’ Awareness of Cybersecurity Threats in the Digital Era - Matandatu, Stevani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The rapid advancement of digital technology has significantly increased the use of mobile banking services. These services offer convenience but also raise the risk of cybersecurity threats. This study aims to identify the factors that influence user awareness of cybersecurity threats in mobile banking services in the digital era. A quantitative survey was conducted with 100 active mobile banking users from urban areas in Indonesia. Data were collected through a structured questionnaire that measured cybersecurity knowledge, security behavior and practices, and users’ perception of cyber threat risks. Descriptive statistics and multiple linear regression analysis were used to examine the relationships among the variables. The findings indicate that cybersecurity knowledge, such as understanding phishing, the importance of updating applications, and the risks of using weak passwords, has a significant impact on users’ risk perception. Additionally, security practices such as using different passwords, enabling two factor authentication, and regularly changing passwords also contribute to higher risk awareness. Social and environmental factors, including formal education, workplace training, and community discussions, play an important role in enhancing digital literacy and user awareness. These results highlight the need for an integrated approach that combines continuous education, accessible security technologies, and a supportive social environment to strengthen mobile banking security awareness. The study recommends intensifying educational programs adapted to users’ levels of digital literacy and developing automated security features that encourage protective behavior. This research provides empirical support for the development of effective cybersecurity protection policies and strategies in the digital age.